Adenomatoid tumor of the uterus; report of a rare incidentaloma - Kundu, Reetu; Mohan, Harsh; Sehgal, Alka; Takkar, Navneet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Adenomatoid tumor of the uterus is extremely rare and usually an incidental finding in the uteri removed surgically for some other cause as in the present case. The histogenesis of this tumor has been controversial ever since its discovery, although the most favored and proposed is a mesothelial origin. Grossly it is usually mistaken for a leiomyoma. The tumor may have a variety of histomorphologic patterns with rare bizarre appearances, at times leading to an erroneous diagnosis of metastatic adenocarcinoma.